2011
DOI: 10.1007/s11262-011-0639-z
|View full text |Cite
|
Sign up to set email alerts
|

An RNA-dependent RNA polymerase gene of a distinct Brazilian tospovirus

Abstract: The tospoviral RNA-dependent RNA polymerases (RdRp), or L proteins, perform several conserved functions during virus replication in host cells. In this study, an L segment sequence of 9,040 bp from a new tospovirus (family Bunyaviridae) naturally infecting bean (Phaseolus vulgaris L.) plants was characterized. It encodes the largest RdRp gene known yet for this genus, with deduced 2932aa and a molecular mass of approximately 336 kDa. A Lysine-rich C-terminal extension was found, which apart from our isolate, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
4
10
0
Order By: Relevance
“…These results confirmed that BeNMV is particularly distinct from other characterized tospovirus species, as previously suggested using only the RNA-dependent RNA polymerase (RdRp) protein [15]. The correspondence between N and RdRp protein phylogeny suggests that both genes can be used to understand the phylogenetic relationships among tospoviruses, with the advantage of using a more conserved region (RdRp) and, consequently, simplifying the PCR-based strategies for detection of highly divergent new viruses.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…These results confirmed that BeNMV is particularly distinct from other characterized tospovirus species, as previously suggested using only the RNA-dependent RNA polymerase (RdRp) protein [15]. The correspondence between N and RdRp protein phylogeny suggests that both genes can be used to understand the phylogenetic relationships among tospoviruses, with the advantage of using a more conserved region (RdRp) and, consequently, simplifying the PCR-based strategies for detection of highly divergent new viruses.…”
Section: Resultssupporting
confidence: 84%
“…As previously observed [13], [15], the American and Eurasian clades formed distinct monophyletic groups (bootstrap values of 98 and 98, respectively), and the Peanut chlorotic fan-spot virus (PCFSV) [28] and Groundnut yellow spot virus (PYSV) [29] (divergent viruses isolated from peanut) formed a monophyletic basal clade among tospoviruses. Crucially, the BeNMV was related to SVNaV, forming a well-supported monophyletic clade (bootstrap value of 93%), which was consistent with their pairwise distances (Table S2).…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations